Inspirational thoughts can drive a positive behavioural change: The perceived benefits of Mann Ki Baat (Inner thoughts) messages amongst the smallholder Indian farmers - GAUTAM, U S; SINGH, RANJAY K; MEERA, SHAIK N; KUMAR, SURESH; SINGH, ANSHUMAN; BURMAN, R R; PATHAK, HIMANSHU (The Indian Journal of Agricultural Sciences, 2023)
Farmers are convinced if the message has trustworthiness and is from credible communication sources. In this context, we considered the Mann Ki Baat programme narrated by the Hon’ble Prime Minister as a key motivational factor in shaping the smallholder farmers’ perception vis-a-vis the importance of innovative learning, mobilization, and better access and adoption of the institutional resources (e.g. agri-inputs, agro-advisories, skill development etc.) as efficient means to adapt to the emerging challenges. This study was carried out to draw insights and lessons on the pattern and frequency of listening to the various Mann Ki Baat topics by the smallholder farmers, and how this led to a behavioural change for the sustainable management of agri-food systems. The observations recorded from 1,364 farmers from various states of India revealed that natural farming, conservation of natural resources and willingness to adopt the integrated farming systems (diversification) were the most preferred topics of Mann Ki Baat by the smallholder farmers. Notwithstanding their relatively poor adaptive capacity, a majority of the sample farmers agreed that ideas communicated through Mann Ki Baat were easily implementable on their farms. The perceived trickle-down effect of Mann Ki Baat was also instrumental in mobilizing the farmers to better access the institutional resources, facilitated by an enabling networking with the KVKs and other institutions. This process of change may augur well for enhanced reciprocal learning, enabling the smallholder farmers to better cope up with suit of stresses. It also emerged that mass scale awareness programmes such as Mann Ki Baat by the Hon’ble Prime Minister of India were seen as credible sources of inspiration, paving the way for sustainable agricultural production and entrepreneurial development in the rural hinterlands of India.